The Implementation of Educational Operational Funding (BOP) Policy for Enhancing Educational Facilities and Infrastructure at SMKN 60 West Jakarta - Erika Radina Sipayung; Ratri Istania; Edy Sutrisno (International Publisher (YAPENBI), 2025)
According to Law Number 20 of 2003, education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble morals, and skills needed by themselves, society, nation and state. Every citizen aged 6 (six) years can participate in the compulsory education program. Biaya Operasional Pendidikan (BOP) are the main source of school financing budgeted through the DKI Jakarta Regional Budget. The DKI Jakarta Provincial Government organizes a BOP assistance program for State Education Units. The DKI Jakarta Provincial Government through the BOP fund assistance program must accommodate school needs related to the provision of facilities and infrastructure in education units. SMKN 60 West Jakarta is the research locus because it is the only Tourism SMKN that has the largest budget for maintaining its facilities and infrastructure in the West Jakarta Education Sub-dept. II Region in the 2023 Fiscal Year and the only SMKN out of a total of 63 SMKNs in DKI Jakarta that received rehabilitation funds for repairs and demolition of school buildings in the 2022 Fiscal Year. Based on these conditions, an analysis of the strategy for implementing the BOP funding policy at SMKN 60 West Jakarta will be carried out along with the supporting and inhibiting factors for the implementation of the policy. It is hoped that the implementation of the BOP funding policy will be effective, transparent and accountable in educational units, especially at SMKN 60 West Jakarta.